Floral Composition and Timber Stock of Forest In The Samar Island Natural Park - Quimio, Justino M. (Annals of Tropical Research, 2016)
Samar Island Natural Park (SINP) is the most important biodiversity refuge Samar Island. This assessment characterized floral diversity status in SINP and provided recommendations on how such resources can be better managed and protected against destruction. Five watersheds, namely: Taft, Can-avid, Basey, Suribao and Catubig were sampled. In each watershed, a transect line with 25 plots spaced at 200 m interval was used in the survey. Plot size was 20m x 20m. Trees 10 cm in diameter at breast height (DBH) and bigger were measured for stem diameter, merchantable height and tree height. This was for computation of timber volume. The species composition in 3 vegetative layers, such as tree layer, undergrowth and ground layer, was determined using the standard Braun-Blanquet methodology. The forest stands in the five watersheds was dominated by dipterocarp species. Of the 212 timber tree species in the tree layer, 35 species had diameter of at least 60 cm. Eighty-six percent of individual trees were dipterocarps, in 14 species. Shorea squamata and Shorea polysperma was the most frequent. Non-dipterocarp species dominated in number at the lower DBH range, particularly in the 10-20 cm and 21-40 cm DBH range. The forest of Samar still has high volume of commercial-size timber. Forests in the 5 watersheds differed in species composition and structure. The absence of access roads to interior barangays contributed to the conservation of forests. The transport system, such as presence of access road and connecting transport facilities to the main roads had influence to the degree of poaching activities. Areas that had access only through motorboats in shallow river had lowest incidence of poaching.